The Urban and Rural Cadastre of Valle del Cauca, 1919: The Urban and Rural Cadastre of Valle del Cauca, 1919: a bit of the written performance of the state - mera, hansel; Sánchez Salcedo, José Fernando (Sociedad y Economía, 2025)
This article brings to light the 1919 Urban and Rural Cadastre of Valle del Cauca, an unpublished document recently discovered in the Central Archive of the Governorship of Valle del Cauca. To analyze this histori cadastre, this article first described some key elements regarding the heuristics of its documentary typology and the main features of the Government written performance. Secondly, it presents a general overview of the urban and rural issues presented in light of its data. Finally, it gives a detailed transcription of the entire document, including the number of owners, building materials and specifications, type of crops, and number of farming land, etc.